Associação de fungos ectomicorrízicos com espécies florestais nativas do estado do Rio Grande do Sul - Andreazza, Robson (2006)
The work was development in Forestry Fepagro, Santa Maria, RS and in Laboratory of Biology and Microbiology of Soil and Environment Prof. Marcos Rubens Fries, from Department of Soil of Federal University of Santa Maria. First, the objective was to identify mycorrhizal associations in six native forestry species of Rio Grande do Sul State. This research was conducted in tree seasons of the year, in six native forestry species of State of Rio Grande do Sul. The roots were processed and analyzed according to mycorrhizal colonization type. The sporocarps found of native ectomycorrhizal fungi were identified, isolated and multiplied. The studies species were Araucaria angustifolia (Bertol.) Kuntze), Enterolobium contortisiliquum (Vell.) Morong.), Peltophorum dubium (Spreng) Taub.), Tabebuia chrysotricha (Mart. ex DC.) Standl.), Tabebuia impetiginosa (Mart.) Standl.), Apuleia leiocarpa (Vogel) J.F. Macbride). The forestry species didn t show ectomycorrhizal colonization in native conditions, although, it was found in some sporocarps near to some plants. It was observed the presence of associations with endomycorrhizal fungi in all species. The following study had the objective to test the possibility to form associations with ectomycorrhizal fungi and Apuleia leiocarpa and, in the fungi isolated UFSM RA 2.8 and UFSM RA 3.6 from Fepagro Forestry, respectively. These fungi were classified as Suillus sp. and Scleroderma sp. respectively. The fungi UFSC Pt 116 (Pisolithus microcarpus) and UFSC Pt 24 (Pisolithus sp.), were from of Federal University of Florianópolis, including the treatment without fungi. In Apuleia leiocarpa the fungi UFSM RA 3.6 was substituted by UFSC Sc 124 (Scleroderma sp.) fungi. It was analyzed seedling length, brash mass of aerial part and root, dry mass of part aerial, length and root and mycorrhizal colonization. It was observed the formation of ectomycorrhizal association in little plants of Apuleia leiocarpa and in Peltophorum dubium when inoculated with the ectomycorrhizal fungi Suillus sp.(UFSM RA 2.8). Furthermore, the results showed the best development in Apuleia leiocarpa in high plants, brash mass of aerial part and root, dry mass of part aerial. The Apuleia leiocarpa showed ectomycorrhizal association with isolated UFSM RA 2.8, in vitro . The Peltophorum dubium showed evidence that is possible have ectomycorrhizal associations with the isolate UFSM 2.8 in laboratory conditions.